Child Friendly Village Program as an Effort to Prevent Crimes of Violence against Children in Temusai Village, Siak Regency - Elmayanti Elmayanti; Evi Deliana; Mukhlis R (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Kampung Temusai has been designated as a village worthy of children designated by the Bungaraya District. The formulation of the problem in this study is, what are the forms of child-friendly village programs as an effort to prevent child abuse in Temusai village and what are the factors that become obstacles in the implementation of the child-friendly village program and what are the efforts done in coming these obstacles. This research was conducted in Temusai Village. This type of research is sociological juridical with an emphasis on field research. The sociological juridical approach is carried out because the problems studied revolve around how the law applies in society. Judging from its nature, this research is descriptive, because it intends to describe the reality clearly and systematically. The Child Friendly Village Program that has been carried out in Temusai Village is the Community-Based Integrated Child Protection Campaign (PATBM), Maghrib study Program, Collaboration and coordination with various parties in supporting the Child Friendly District Program (KRA). The factors that become obstacles in implementing the child-friendly village program in Temusai village are Lack of Professional Human Resources, Limited technical guidance, Limited budget in running existing programs, Lack of supporting facilities and infrastructure for the Child Friendly Village Program and Lack of awareness community in supporting the Child Friendly Village program. Efforts made to overcome obstacles in the implementation is Coordinating with the local government regarding the budget which is still very minimal,